Re-Heating Effect on the Enhancement of Plasma Emission Generated from Fe Under Femtosecond Double-Pulse Laser Irradiation - 王莹 陈安民 李苏宇 隋来志 刘敦利 李舒畅 李贺 姜远飞 金明星 (Plasma science & technology, 2016)
In this paper, we present a study on the effect of inter-pulse delay using femtosecond double-pulse laser-induced breakdown spectroscopy in a collinear geometry. The temporal evolution of spectral intensity is performed for the lines of Fe I 423.60 nm, Fe I 425.08 nm and Fe I 427.18 nm. It is found that, by selecting appropriate inter-pulse delay, the signal enhancement can be significantly increased compared with the single-pulse case. A three-fold enhancement in the current experiment is obtained. The plasma temperature and electron density are also investigated based on the theory of Boltzmann plot and Stark broadening. We attribute the main mechanism for emission enhancement to the plasma re-heating effect.